The History of the Discovery of Red Beans (Phaseolus Vulgaris L.) And It’s Meaning - Tuychiyev Dilfuza Sidikjanovna; Yunusova Lazokathon Kimsanboevna (American Journal of Biology and Natural Sciences, 2025)
The article provides information on the significance, origin, distribution, biological properties and varieties of common beans (Phaseolus vulgaris L.). It is also emphasized that common beans are an important legume and vegetable crop rich in high-quality protein, microelements, vitamins and antioxidants.